Evaluating the impact of the target area concentration (TAC)programme for beef cattle production - Man, Norsida; Ahmad, Shamsuddin (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
A cattle farming is one of the main activities in the agriculture sector of Malaysia. It is the source of national beef production pioneered by three sources, namely the production system dominated by a majority of traditional systems of the past system of free practice that has contributed more than 50% of national beef production. The rest is from the intensive system of cattle feedlots and integrated farming systems. The objective of this study is to investigate and evaluate the effectiveness of Target Area Concentration (TAC), a program conducted by the Department of Veterinary Services(DVS). In particular, this study is to 1) evaluate the achievement of the program; 2) evaluate the effectiveness of development programs through LTJ method; 3) identify the levels of achievement in the CIPP (Context, Input, Process and Product); 4) identify the side effects of the implementation of the TAC program; 5) evaluate the respondents' perceptions on the acceptance of programs undertaken to improve the well-being. The study found that there is an increase in the number of participants from year to year, the number of TAC and area of coverage of livestock has also increased by the year. With such increment, the cattle parent population is increased and so does the production of meat. For meat production in TAC program, achievements can only be achieved at the level of 14% of 5,300.83 ton metric and only half of the targets of the TAC program of 28% (10.710 metric tonnes) in 2008. The national meat production targets for the year amounted to 38.250 metric ton. Through the TAC Program, 73.8% of respondents have indicated that their income has increased. In terms of the estimated cost savings of using herbicides, respondents felt that they could save 41-60% while for the company is 21-40%. Other than that, land can be used optimally in permanent crops, especially oil palm with the implementation of integrated livestock systems. In addition, the majority of respondents indicated that no pollution occurred as a result of this activity. Overall, the TAC program was expected impact. Even though the achievement of this program is acceptable, more space for improvement and superior are needed.